2014
DOI: 10.1155/2014/616817
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-Binding Lectin in Cardiovascular Disease

Abstract: Cardiovascular disease remains the leading cause of mortality and morbidity worldwide so research continues into underlying mechanisms. Since innate immunity and its potent component mannan-binding lectin have been proven to play an important role in the inflammatory response during infection and ischaemia-reperfusion injury, attention has been paid to its role in the development of cardiovascular complications as well. This review provides a general outline of the structure and genetic polymorphism of MBL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 118 publications
2
22
0
Order By: Relevance
“…More recent evidences in humans confirmed the beneficial effects of MBL deficiency in ischemic diseases: the reduced mortality for acute myocardial infarction reported in patients with MBL deficiency undergoing percutaneous coronary intervention; the long-lasting protection toward cerebral ischemia after the inhibition of MBL; the higher levels of MBL found in patients with unstable angina; and finally, the fatal outcome in an MBL deficient patient with myocardial infarction after MBL transfusion [31].…”
Section: Mbl and Cardiovascular Diseases: A Conflicting Relationshipmentioning
confidence: 73%
See 1 more Smart Citation
“…More recent evidences in humans confirmed the beneficial effects of MBL deficiency in ischemic diseases: the reduced mortality for acute myocardial infarction reported in patients with MBL deficiency undergoing percutaneous coronary intervention; the long-lasting protection toward cerebral ischemia after the inhibition of MBL; the higher levels of MBL found in patients with unstable angina; and finally, the fatal outcome in an MBL deficient patient with myocardial infarction after MBL transfusion [31].…”
Section: Mbl and Cardiovascular Diseases: A Conflicting Relationshipmentioning
confidence: 73%
“…Myocardial reperfusion after ischemia triggers an inflammatory response that paradoxically counteracts the beneficial effects of the improved blood flow [31] and recruits either inflammatory or innate immunity mediators. Subsequently, studies in the mice model confirmed the disadvantageous effects of high biological activity of MBL in myocardial ischemic diseases, e.g., a high deposition of the protein in ischemic hearth, and the advantages of reduced MBL activity, e.g., the protection by cardiac damage and the reduction of the infarct area in MBL deficient mice [32].…”
Section: Mbl and Cardiovascular Diseases: A Conflicting Relationshipmentioning
confidence: 99%
“…The complement system may be a key mechanism in the host response to CPB, and that could include the lectin pathway. Its potent activator, mannose‐binding lectin, plays an important role in the development of cardiovascular disease and ischaemia–reperfusion injury . Lectin pathway involvement in the reaction to CPB during adult cardiac surgery was reported originally by Hoedemaekers et al .…”
Section: Discussionmentioning
confidence: 98%
“…At baseline, 28% of the Cohort on Diabetes and Atherosclerosis Maastricht (CODAM) participants had CVD and 16% had CVE. In Table I 1,4,7,10 For this reason, the A/0 and 0/0 individuals were combined into 1 group in the regression analyses.…”
Section: Study Populationmentioning
confidence: 99%
“…1 Several large studies that investigated mannose-binding lectin (MBL) in relation to the risk of CVD have yielded contradictory findings. Studies that investigated MBL genotypes as proxies for circulating MBL consistently found that genotypes that result in low or deficient MBL were a risk factor for the development of CVD.…”
mentioning
confidence: 99%